2024
DOI: 10.1186/s10194-024-01730-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide, VE-cadherin, HMGB1, and HIF-1α levels are elevated in the systemic circulation in chronic migraine patients with medication overuse headache: evidence of leaky gut and inflammation

Doga Vuralli,
Merve Ceren Akgor,
Hale Gok Dagidir
et al.

Abstract: Objective Medication overuse headache (MOH) was recently shown to be associated with leaky gut in rodents. We aimed to investigate whether chronic migraine (CM) patients with MOH have elevated lipopolysaccharide levels and inflammatory molecules in blood circulation. Materials and methods The study included women participants (40 CM patients with NSAID overuse headache, 35 episodic migraine (EM) patients, and 20 healthy non-headache sufferers). Mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The genus Bacteroides is reduced in a treatment-nonresponsive depressed subgroup compared to in healthy controls [78], and it has a rich arsenal for metabolizing more complex carbohydrates, including glycans of human mucin [166,167]. In agreement with this hypothesis, Vuralli et al [168] reported that an increased intestinal permeability, probably related to gut microbiota changes, would impact the response to anti-CGRP monoclonal antibodies in people with migraine. Figure 2 shows the microbiota-GBA crosstalk in migraine and depression.…”
Section: Potential Mechanisms Related To Microbiota and Relevant To T...mentioning
confidence: 86%
“…The genus Bacteroides is reduced in a treatment-nonresponsive depressed subgroup compared to in healthy controls [78], and it has a rich arsenal for metabolizing more complex carbohydrates, including glycans of human mucin [166,167]. In agreement with this hypothesis, Vuralli et al [168] reported that an increased intestinal permeability, probably related to gut microbiota changes, would impact the response to anti-CGRP monoclonal antibodies in people with migraine. Figure 2 shows the microbiota-GBA crosstalk in migraine and depression.…”
Section: Potential Mechanisms Related To Microbiota and Relevant To T...mentioning
confidence: 86%